Concurrent Diabetic Ketoacidosis in Hypertriglyceridemia-Induced Pancreatitis: How Does It Affect the Clinical Course and Severity Scores?. Issue 10 (November 2017) - Wang, Yuchen; Attar, Bashar M.; Hinami, Keiki; Jaiswal, Palashkumar; Yap, John Erikson; Jaiswal, Radhika; Devani, Kalpit; Simons-Linares, Carlos Roberto; Demetria, Melchor V.
Abstract : Objectives: Concurrent diabetic ketoacidosis (DKA) is highly prevalent in patients with hypertriglyceridemia-induced pancreatitis (HP). Diabetic ketoacidosis could potentially complicate the diagnosis, management, and prognosis of HP. This study aimed to directly compare the clinical course of HP with and without DKA and assess the outcomes of frequently used severity-prediction scores in such population. Methods: We retrospectively analyzed 140 patients with HP; 37 patients (26.4%) had concurrent DKA. We compared epidemiologic characteristics, initial laboratory values, and clinical courses between the DKA and non-DKA groups. Bedside Index for Severity in Acute Pancreatitis score, Sequential Organ Failure Assessment score, Ranson criteria, Acute Physiology and Chronic Health Evaluation II (APACHE II) score, and Marshall score were calculated and compared between groups. Results: We observed more acute kidney injury in the DKA group. Patients with DKA more likely required intensive care unit admission, received intravenous insulin, and were discharged on subcutaneous insulin. Ranson criteria and APACHE II score were significantly higher with DKA. Conclusions: Concurrent DKA does not affect length of stay, in-hospital mortality, and readmission rate in patients with HP. Higher Ranson criteria and APACHE II score likely reflected derangement of clinical parameters secondary to DKA rather than true severity of pancreatitis in such population.